La Formación de Emprendedores Sociales desde Algunos Programas de Contaduría Pública (2019)
Social entrepreneurship is based on initiatives that promote sustainable solutions while benefiting marginal sectors of society; In this order of ideas, this article aims to describe the contribution of public universities in the training of professionals with social commitment, emphasizing in the actions executed from public accounting programs to encourage the emergence of ideas that generate a significant change. In this way, the research started from a documentary review through which social entrepreneurship was contextualized at a national level based on data issued by the global competitiveness index and the national and departmental development plans. Likewise, the profile of the social entrepreneur was analyzed in comparison with the entry and exit profiles of the public accounting students, for which three public universities and a private university of the department of Cundinamarca and Bogotá DC were taken as examples, in which the academic program in question was offered, which allowed grouping the competences that allow the Public Accountant to undertake socially by identifying the degree of compliance of each university regarding each competence.